Fish genetics and aquaculture biotechnology (Science Publishers, 2005)
To feed the growing world population, water is looked upon as a major source of food production. This book is an attempt to bring out a comprehensive volume on Fish Transgenesis, Chromosome Engineering and Sex Control, Molecular Endocrinology, Microbal Diseases and Vaccines, and Bioactive Compounds.